2021
DOI: 10.3390/w13202854
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Procedures for Separating Microplastics from Sediments

Abstract: The separation of microplastics from environmental matrices is still challenging, especially for sediments where microplastics can accumulate affecting benthic organisms. Many authors have adopted different procedures, but their effectiveness has been rarely compared. The present study aims to compare the recovery rate of three different methodologies for the separation of dense microplastics from fine sediments and provide insights about contamination processes occurring in microplastic separation techniques.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
(71 reference statements)
1
7
0
Order By: Relevance
“…Interestingly, the frequency of smaller microplastics in river water samples from both the Kemena and Niah rivers was consistently higher than in sediment samples. This observation is consistent with previous research, which suggested that buoyant plastic particles with a lower density than water can remain suspended in the water column, while denser particles can settle down onto the river bed and eventually sink into the sediments [21,22]. The higher percentage of the smallest microplastics detected in the sediment samples of the Kemena and Niah rivers highlights the fact that smaller plastic particles are more prone to migrate into sediments and deep water.…”
Section: Size Of Microplasticssupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, the frequency of smaller microplastics in river water samples from both the Kemena and Niah rivers was consistently higher than in sediment samples. This observation is consistent with previous research, which suggested that buoyant plastic particles with a lower density than water can remain suspended in the water column, while denser particles can settle down onto the river bed and eventually sink into the sediments [21,22]. The higher percentage of the smallest microplastics detected in the sediment samples of the Kemena and Niah rivers highlights the fact that smaller plastic particles are more prone to migrate into sediments and deep water.…”
Section: Size Of Microplasticssupporting
confidence: 92%
“…Furthermore, the size distribution of microplastics in river water and sediments highlights the different processes that control their transport and fate in the environment. [21,22].…”
Section: Colour Of Microplasticsmentioning
confidence: 99%
“…The NaI solution showed the highest recovery of 91.2% (PET), 93.7% (PA), and 91.7% (PU) for the separation of textile microplastics among all tested solutions. However, NaI is relatively expensive, and its solution is hazardous to the environment [ 58 ]. In addition, during the testing process, it was also found that NaI is highly oxidizing, and its use can lead to oxidation of the filter membranes to yellow and black colors, which has a greater impact on the subsequent visual identification and qualitative analysis ( Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…(3) The efficiency of MPs isolation is inversely proportional to particle size; the smallest proportion of isolated particles are those with smaller dimensions [135]; (4) Due to their hydrophobic nature, the particles often coalesce into agglomerates to which various pollutants and microorganisms are adsorbed and form biofilms [41].…”
Section: Density-based Approachmentioning
confidence: 99%